2022
DOI: 10.3390/diagnostics12061338
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antigen Test Results to Infer Active or Non-Active Virus Replication Status in COVID-19 Patients

Abstract: We used nasopharyngeal swab samples of patients with a symptomatic (n = 82) or asymptomatic (n = 20) coronavirus disease 2019 (COVID-19) diagnosis to assess the ability of antigen detection tests to infer active (potentially transmissible) or inactive (potentially non-transmissible) infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Using the subgenomic RNA (sgRNA) as an active replication marker of SARS-CoV-2, 48 (76.2%), 56 (88.9%), and 63 (100%) of 63 samples with sgRNA positive resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The choice to use the antigen-test solution in 2022 for RT-qPCR was caused by the emergence of the Omicron variant and the second wave of COVID-19 cases. The number of cases rose quickly, and antigen tests were more efficient in detecting individuals with active viral replication [ 31 , 32 ]. In addition, this system would avoid the need for collecting three nasopharyngeal samples from the same person, considering that one sample was already used for RT-LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…The choice to use the antigen-test solution in 2022 for RT-qPCR was caused by the emergence of the Omicron variant and the second wave of COVID-19 cases. The number of cases rose quickly, and antigen tests were more efficient in detecting individuals with active viral replication [ 31 , 32 ]. In addition, this system would avoid the need for collecting three nasopharyngeal samples from the same person, considering that one sample was already used for RT-LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed in a recent study, in which Veritor showed a sensitivity of 74% when compared to cell culture ( 25 ). Similarly, a study on the diagnostic performance of different Ag-RGT by contrasting the results with detection of subgenomic RNA suggests their ability to determine the presence or absence of replication-competent, thus potentially transmissible, virus ( 26 ). In order to implement these findings to the clinical practice, one should take into account the role of infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Still, testing of asymptomatic individuals is recommended in some settings ( 24 ) and NAAT techniques may not represent an appropriate standard reference in this population as they do not distinguish infectious and non-infectious virus, thus failing to identify persons with non-infectious SARS-CoV-2 infection in whom isolation could be spared. In contrast, recent studies suggest an association between positive Ag-RDT results and cell culture positivity, as well as the presence of subgenomic RNA, a surrogate for the presence of viable virus ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 87%